Orientation of the Eruption Fissures Controlled by a Shallow Magma Chamber in Miyakejima - Geshi, Nobuo; Oikawa, Teruki (Frontiers in Earth Science, 2016)
Orientation of the eruption fissures and composition of the lavas of the Miyakejima volcano is indicative of the competitive processes of the regional tectonic stress and the local stress generated by the activity of a magma plumbing system beneath the volcano. We examined the distributions and magmatic compositions of 23 fissures that formed within the last 2800 years, based on a field survey and a new dataset of 14C ages. The dominant orientation of the eruption fissures in the central portion of the volcano was found to be NE-SW, which is perpendicular to the direction of regional maximum horizontal compressive stress (σHmax). Magmas that show evidence of mixing between basaltic and andesitic compositions erupted mainly from the eruption fissures with a higher offset angle from the regional σHmax direction. The presence of a dike pattern perpendicular to the direction of maximum compression σHmax is an unusual and uncommon feature in volcanoes. Here we investigate the conditions possibly controlling this unexpected dike pattern. The distribution and magmatic compositions of the eruption fissures in Miyakejima volcano highlight the tectonic influence of shallow magma chamber on the development of feeder dikes in a composite volcano. The presence of a shallow dike-shaped magma chamber controls the eccentric distribution of the eruption fissures perpendicular to the present direction of σHmax. The injection of basaltic magma into the shallow andesitic magma chamber caused the temporal rise of internal magmatic pressure in the shallow magma chamber which elongates in NE-SW direction. Dikes extending from the andesitic magma chamber intrude along the local stress field which is generated by the internal excess pressure of the andesitic magma chamber. As the result, the eruption fissures trend parallel to the elongation direction of the shallow magma chamber. Some basaltic dikes from the deep-seated magma chamber reach the ground surface without intersection with the andesitic magma chamber. These basaltic dikes develop parallel to the regional compressive stress in NW-SE direction. The patterns of the eruption fissures can be modified in the future as was observed in the case of the destruction of the shallow magma chamber during the 2000 AD eruption.